IQF Based Curriculum in Islamic Universities In Indonesia - Jufriadi Jufriadi; Efendi Efendi (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study aims to find out (1) how Islamic universities implement the IQF-based curriculum; (2) What are the perceptions of lecturers and students towards the IQF-based curriculum; (3) What factors can hinder the implementation of the IQF-based curriculum. Data for this study were collected using interviews, observations, documents, and Focus Group Discussions. The data were analyzed qualitatively by using descriptive and thematic analysis in which the process is in five steps; familiarization, codification, review themes, finalize themes, and report writing. The study revealed that the universities did both macro and micro-level preparation for implementing the IQF curriculum, while both students and lectures still indicated some limitations and informed some constraints in implementation.